Anti-Hu Antibody-Associated Adie's Pupil and Paraneoplastic Sensorimotor Polyneuropathy Caused by Primary Mediastinal Small Cell Carcinoma - Zhang, Lei; Luo, Si; Jin, Hui; Lv, Xueman; Chen, Jiajun (Frontiers in Neurology, 2019)
We report a woman with unilateral Adie’s pupil associated with peripheral sensorimotor polyneuropathy, elevated anti-Hu antibody and primary mediastinal small cell carcinoma (SCC). To our knowledge, this is the first report of Adie’s pupil in a patient with mediastinal SCC. Although rare, Adie’s pupil and sensorimotor polyneuropathy may be the first manifestation of cancer. Its rapid recognition facilitates an early diagnosis and treatment.